REVEALING THE IDEOLOGY BEHIND THE MINIMALIST OF RESIDENTIAL DEVELOPMENT PRACTICES IN SOUTH KUTA - Pande Artadi, I Made; Anom Kumbara, A.A. Ngurah; Rumawan Salain, Putu; Gde Pujaastawa, Ida Bagus (E-Journal of Cultural Studies; Volume 13, Number 2, May 2020, 2020)
The practice of developing minimalist residential design in South Kuta is increasingly being accepted massively in Balinese society. The residential design carries the values ??of modernity and is independent of the environmental context and values ??of Balinese culture. Its physical appearance is geometric, simple, clean and without ornamentation. The minimalist residential development and acceptance is contrary to the Bali Provincial Regulation No. 05 of 2005 concerning Architectural Buildings which require all buildings including residential buildings to display Balinese style. Massive acceptance of this residence has implications in the dimensions of Balinese environmental, social and cultural identity. The research objective is to uncover the ideology behind developing and accepting minimalist housing in South Kuta; and reveal its implications for Balinese culture. For this purpose, the research approach used is the Cultural Studies and Design Studies approach. The type of data collected is qualitative data which is then analyzed by interpretive qualitative analysis methods. To understand and interpret data, deconstruction theory, semiotics and identity theory are used. The results of the study revealed that there are three ideologies behind developing and accepting minimalist occupancy in the middle of South Kuta society are capitalist, materialistic and functional-rationalist ideologies. The implication of the receipt of this residence in the community is the chaos of traditional residential values ??and deprivation of Balinese identity.  Keywords: Ideology, minimalist architecture, functionalism-rationalism.